SCHOOL PLANT CONSTRUCTION, UTILIZATION, MAINTENANCE AND SCHOOL EFFECTIVENESS IN KEBBI SECONDARY SCHOOLS, NIGERIA - Manga, Sani Dantani (Sokoto Educational Review, 2011)
This study investigated the relationship between school plant construction, utilization, maintenance and school effectiveness in Kebbi State secondary schools, Nigeria. The study adopted the descriptive research design conducted ex-post-facto. Stratified and simple random sampling techniques were used to select 63% of 41 schools and 69% of 500 participants for this study respectively. A validated questionnaire with a reliability index of .79 was used to generate data. Results of multiple regression and analysis of variance show that school plant construction, utilization and maintenance were positively, highly and significantly correlated with school effectiveness with calculated revalue of 76.68. But in view of the poor quality of the school environment in Kebbi state secondary schools, education policy and management practices should focus on improving the quality of school plant for the attainment of school effectiveness.